Wire and arc additive manufacturing: equipment development and parts characterization - Rodrigues, Tiago Miguel André (2018)
Wire and arc additive manufacturing (WAAM) is finding applications in different industrial sectors where it shows to be competitive compared to laser based additive manufacturing technologies. Two major advantages are associated to WAAM: it is a low capital investment technology with reduced running and maintenance costs and allows to manufacture parts with insipient or no porosities. This study aimed at testing and validating a three-axis positioning system designed and manufactured at Mechanical Technology Group of Mechanical and Industrial Engineering Department at Nova University. The major characteristics of the developed system are the following: 4.5 m3 working space, a maximum travel speed of 59 mm/s for the X and Y axes and of 2 mm/s for the Z axis. A maximum positional deviation of 0.02 mm, a minimal travel speed deviation of 0.24 mm/s and a displacement of 0.2 mm of the welding torch due to vibrations during a unidirectional movement. The equipment was validated by manufacturing thin walls by deposition of a high strength low alloy (HSLA) steel wire with Gas Metal Arc Welding (GMAW), monitoring the thermal cycles by infrared thermography to evaluate them in different layers. Geometrical, microstructural and mechanical characterization of parts was performed. Manufactured parts exhibited good surface finishing measured by the surface waviness that was around 300 μm and no internal defects were observed. Parts were isotropic as far as microstructural features and mechanical performance are concerned. The microstructure was mainly constituted by acicular ferrite and perlite with hardness below 320 HV. Energy dispersive spectrometry was performed, and no element loss was identified. Ultimate tensile strength varied between 700 and 809 MPa, depending on the process parameters. Resistance to impact was assessed by Charpy V impact tests with reduced size specimens and the absorbed energy registered was of 15 and 18 J, in longitudinal (Y) and normal (Z) directions, respectively. A ductile fracture surface was observed which is also a relevant indicator of mechanical performance of parts produced by WAAM in a HSLA steel.